Regio-isomerism directed electrocatalysis for energy efficient zinc-air battery - Mukhopadhyay, Sanchayita; Devendrachari, Mruthyunjayachari Chattanahalli; Kanade, Sandeep C.; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Thotiyl, Musthafa Ottakam (iScience, 2022)
We have investigated the role of ligand isomerism in modulating the mechanisms and kinetics associated with charge/ discharge chemistry of an aqueous metal-air battery. The dominant electron-withdrawing inductive effect (-I effect) and the diminished electron-withdrawing resonance effect (-R effect) in the alpha-NO2 isomer noticeably diminishes the rate of oxygen reduction (ORR) and oxygen evolution reactions (OER) on the catalytic Co-center. In their beta-counterpart, the cumulative -I and -R effects noticeably enhance the OER and ORR kinetics on the same catalytic Co-center. Therefore, the regioisomerism of the -NO2 functionality amplifies the kinetics of ORR/OER without influencing their mechanistic pathways. When isomeric electrocatalysts are integrated to aid the charge chemistry of a Zn-air battery, the overpotential could be decreased by similar to 250mV with beta-NO2 isomer leading to a round-trip efficiency as high as 60%. This work contributes to the design of novel molecular platforms to target the overall round-trip efficiency of energy storage and conversion devices.

Unusual ligand assistance in molecular electrocatalysis via interfacial proton charge assembly - Mukhopadhyay, Sanchayita; Kottaichamy, Alagar Raja; Chame, Pallavi Vyankuram; Ghosh, Prasenjit; Vinod, Chathakudath Prabhakaran; Makri Nimbegondi Kotresh, Harish; Kanade, Sandeep C.; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2023)
We show that the ability of the ligand to reorganizethe electricdouble layer (EDL) often dominates the electrocatalysis contrary totheir inductive effect in the spectrochemical series, leading to counterintuitiveelectrocatalysis. With water oxidation and chlorine evolution as theprobe reactions, the same catalytic entity with carboxy functionalizedligand exhibited surprisingly higher electrochemical activity in comparisonto the aggressively electron-withdrawing nitro functionalized ligands,which is contrary to their actual location in the spectrochemicalseries. Spectroscopic and electrochemical analyses suggest the enrichmentof catalytically active species in the carboxy substituted ligandvia proton charge assembly in the EDL that in turn enhances the kineticsof the overall electrochemical process. This demonstration of lessobvious ligands becoming indispensable in electrocatalysis suggestsa blind designing of ligands solely based on their inductive effectshould be reconsidered as it will prevent the utilization of the maximumpotential of the molecule in electrocatalysis.